Type D Personality, Concomitant Depressive and Anxiety Disorders, and Treatment Outcomes in Somatic Symptom and Related Disorders: An Observational Longitudinal Cohort Study - de Vroege, Lars; de Heer, Eric W.; van der Thiel, Eva; van den Broek, Krista C.; van Eck van der Sluijs, Jonna F.; van der Feltz-Cornelis, Christina M. (Frontiers in Psychiatry, 2019)
Objective: To establish the prevalence of Type D personality in patients with somatic symptoms and related disorders and to evaluate the association of Type D personality with treatment outcomes. This study explores the effect of Type D personality and its two traits, negative affectivity (NA) and social inhibition (SI). Methods: In this longitudinal observational cohort study, we assessed the prevalence of Type D in 212 patients presenting themselves at a clinic in Tilburg, the Netherlands. We explored psychological and physical treatment outcomes of a multimodal treatment tailored to patient needs in relation to Type D scores. We explored the differences with regard to physical symptoms, anxiety, and depression. We also explored the differences between patients with and without Type D personality who completed treatment with regard to the baseline scores of physical symptoms, anxiety, and depression. We explored the association between Type D personality and treatment outcome using the traditional dichotomous method and the dimensional method (with main effects of NA and SI, and the interaction of NA × SI). Results: Of the 212 patients with Somatic Symptom and Related Disorders (SSRD), those with Type D personality (181: 61.8%) had experienced significantly higher levels of depression [t = 4.404, p < .001] and anxiety [t = 3.757, p < .001]. Of the 212, 187 patients completed treatment. Mean scores improved significantly for the whole patient group after treatment with regard to depression (p < .001), anxiety (p < .001), and physical symptoms (p < .001). At baseline, patients with Type D personality had significantly higher scores in anxiety [F = 15.707, p < .001] and depression [F = 19.392] than patients without Type D personality who completed treatment. After controlling for the high baseline scores with regard to physical symptoms, anxiety, or depression, only the effect of Type D personality on remission of anxiety was significant (OR = .33, p = 0.39). Neither NA and SI nor the interaction of NA × SI was associated with the treatment outcome. Conclusions: This study shows that Type D personality occurs frequently in patients with SSRD. Type D personality only decreases the probability of remission of anxiety as a treatment outcome, and both NA and SI play a role in this. Type D personality did not decrease remission either of physical symptoms or of depression. Hence, both NA and SI factors may be expressions of anxiety mostly in type D.